2017
DOI: 10.1037/rep0000125
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the ICF to understand depressive symptomology in multiple sclerosis: An exploratory systematic review.

Abstract: The ICF can help guide the selection of clinical measures to assess psychosocial functioning in adults with MS and highlight areas necessitating further research and/or intervention. For those reporting depressed mood, this might include interventions premised on supporting activity and participation in addition to reinforcing interpersonal strengths. To enhance the utility of the ICF in MS care, further research is needed to operationalize its domains and to map this framework onto existing measurement tools.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 129 publications
0
11
0
Order By: Relevance
“…To ensure consistent, objective and evidencebased assessment, the reporting quality of each study was assessed (see Dorstyn et al, 2017Dorstyn et al, , 2019 This included study power (one item) and potential for systematic error -namely, detection bias (one item), selection bias (four items), attrition bias (one item) and reporting bias (two items). Items were rated as 'present, 'present with limitations' or 'absent' (not present or unable to be determined).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…To ensure consistent, objective and evidencebased assessment, the reporting quality of each study was assessed (see Dorstyn et al, 2017Dorstyn et al, , 2019 This included study power (one item) and potential for systematic error -namely, detection bias (one item), selection bias (four items), attrition bias (one item) and reporting bias (two items). Items were rated as 'present, 'present with limitations' or 'absent' (not present or unable to be determined).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…The methodological quality of included studies was assessed using a checklist modelled from existing rating tools. [48][49][50][51] Studies were rated on components that are considered critical to clinical research: statistical power (whether the study findings could be attributed to chance); internal validity (degree to which a study minimises bias in measurement and data collection) and external validity (extent to which the study findings can be generalised to the broader SCI population). 52 Two reviewers (KP and DD) were involved in the rating process, with each independently evaluating each study.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Another study proposed the Multiple Sclerosis Impact Profile (MSIP; Wynia et al, 2008 ) an instrument designed to evaluate the perceived impact of MS on functioning. A recent review (Dorstyn et al, 2017 ) highlighted the association between depressive symptoms and reduced social participation in persons with MS. A qualitative study exploring the impact of ICF contextual factors on the daily functioning of Jordanian persons with MS (Hamed et al, 2012 ) identified adequacy of financial and medical resources, religion and community awareness as facilitators, and social stigma as a barrier. Finally, the environmental and personal facilitators of social participation and satisfaction with parenting were investigated among mothers with MS (Farber et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%